MORAL VALUES FOUND IN NAOMI SCOTT’S ‘SPEECHLESS’ SONG LYRICS: AN ATTITUDINAL ANALYSIS USING APPRAISAL THEORY - Gema Gumika Damar Setyaning Djati; Widhiyanto (JELLT (Journal of English Language and Literature Teaching), 2021)
Language is a communication source to deliver information or message. In the communication process, people use language to express idea, opinion, thought, or desire whether in spoken or written form. Following the globalization era, music evolves in human daily life. Through its lyrics, people communicate feelings. Message contained in a song is called as moral value. This research aimed to describe the moral value of an English song viewed from the perspective of appraisal theory. It employed descriptive qualitative approach. The object of the study is the Aladdin’s soundtrack entitled Speechless sung by Naomi Scott released in 2019. The result of the study depicted that the dominant attitude system found is affect system (68.97%) followed by appreciation (17.24%) and judgement (13.79%). The result showed that the songwriters mostly using their feelings in its lyrics. The feeling that dominantly appeared are positive feelings of fearlessness, confidence, and bravery. Furthermore, the prominent attitude of the song is inscribed attitude (72.72%) that indicated directly conveyed, and followed by invoked attitude (27.27%). Related to feminism, the song delivered message in which women should not be underestimated and all the old stigmas which weaken women position should be against in order to achieve equality among genders. Based on the analysis, the song can contribute in material development for the sound argument teaching.